THE EFFECTIVENESS OF USING SONGS IN IMPROVING STUDENTS' GRAMMAR MASTERY : An Experimental Study of Teaching Simple Present and Simple Past Tense in Second Grade Student of a Vocational school in Bandung - Ina Karina, - (2007)
This research paper entitled The Effectiveness of Using Songs in Improving Student's Grammar Mastery was intended to reveal the information about the use of songs in teaching simple present tense and past tense in the second grade of a vocational school student in Bandung. The aim of the research was to find out the effectiveness of using songs in teaching simple present tense and simple past tense. The method of this research was a quantitative research applying true experimental design. The sample was the second grade student of SMKN 9 Bandung. There were 60 students divided into experimental group and control group consisting of 30 students each. Based on the data calculation, t-test score of pretest and posttest in experimental group was -7,884 with and in control group 1,166 with p(sig)=0,253 This result concluded that the null hypothesis in experimental group was rejected because p<0,05 and the null hypothesis in control group was accepted because p>0,05. It indicates that for experimental group the score was significant in 0,000, and for control group the score was no significant between the pre-test and post-test It means that teaching tenses simple present and simple past using songs was effective to be implemented in vocational school In addition, from the students' respond it was discovered that there were some benefits due to the use of songs strategy, they were (a) the lyric of the songs help the students memorize the formula and the example of simple present and simple past tense, (b) The student get the new comfortable and enjoyable atmosphere in learning English, (c) and the students get many new vocabulary. On the other hand, the obstacles were (a) the audio equipment which was used was not very good, (b) and the students felt that the songs were fast and the singer pronunciation was not very clear. For further research, some suggestions were needed to be considered along with the students' perception. First, the chose of songs should be considering the students' level. Second, the chosen of song should adequate example sentences which can be required by the students. Third, the good audio equipments really facilitate the student in learning using songs. And last but not least, the teacher should apply more method and technique which are easy for the students to understand and which are enjoyable for the students.